تعليم اللغة العربية باستخدام الوسائط السمعية الشفوية في مدرسة الهجرة الثانوية الإسلامية المتكاملة الثانية ميدان - Hasibuan, Try Yuana Dewi; Fahrurrozi, Fahrurrozi (Lembaga Yasin AlSys, 2025)
This study aims to analyze the use of the audiolingual method in Arabic language learning to enhance students' speaking skills (mahārah kalām) at SMP IT Al Hijrah 2 Medan. The research focuses on analyzing the use of the audiolingual method and its impact on students' speaking abilities. This study employs a descriptive qualitative approach, collecting data through classroom observation, interviews, and documentation of the learning process. Observations were conducted to understand the use of the audiolingual method, while interviews explored students' and teachers' perspectives on the effectiveness of this method in improving speaking skills. Documentation includes recordings of the learning process, teaching materials, and results of oral tests. The research findings indicate that the use of the audiolingual method has a positive effect on enhancing fluency in speaking, pronunciation accuracy, and students' confidence in speaking Arabic. However, challenges such as limited media were identified.